ANALISIS DAN DESAIN SISTEM PRODUKSI BIOPLASTIK DARI PATI BIJI NANGKA - Rafika Ratik Srimurni; Wilda Harlia Devita; Rahmi Rismayani Deri (Agroindustrial Technology Journal, 2021)
Food packaging technology using plastic continues to experience development towards environmentally friendly packaging, considering that plastic is difficult to degrade. Bioplastic is an alternative developed from natural and environmentally friendly materials such as protein, polysaccharides, and fat. The high carbohydrate content in jackfruit seeds can be used to make plastics that are easily degraded. The composition of the plastic material from a mixture of jackfruit seeds and plasticizers such as glycerol is still not known the exact formula to obtain optimal physical properties and mechanical strength (tensile strength and elongation of break) from bioplastic. This research examines the design and production system and determines the composition of bioplastic materials for the optimization of tensile strength and elongation of break bioplastic from jackfruit seed starch and glycerol. The method used is analysis using BPMN 2.0, system design using the Response Surface Methodology (RSM), as well as verification and validation. The complexity in the bioplastic production system from jackfruit seed starch to maximize the quality of the bioplastics has a relationship between one another which is needed in system analysis and design. The verification results show zero error and zero warning at each modeling step. The best formulation of bioplastics is the composition of starch content to water 6.08% and glycerol content to 30% with a tensile strength value of 0.76 MPa and elongation at break of 6.12%.